PERANCANGAN MULTIMEDIA INTERAKTIF UNTUK MATERI PERLINDUNGAN ANAK TERHADAP PELECEHAN SEKSUAL BERBASIS MOBILE - Ardiana, Dewa Putu Yudhi; Hendrika Loekito, Luciana (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Children have an important role as the next generation of nation's development. Indicating to the roles of children for the future of the nation, so it is deemed necessary to get a chance for them to be best growing. The phenomenon of sexual harassment of children is higest increasingly threathen the growth and development of children. This is due to the lack of knowledge of parents and most of children have less knowledge to prevent sexual harassment. For that purpose, an interactive multimedia android-based application for child protection against sexual harassment has made that can provide danger information and how to prevent child sexual abuse. Applications intended to children of aged 6-12 years. Interactive Multimedia are developed through the stages of Decide, Design, Develop dan Evaluate (DDD-E). In the test results of Black-box testing on mobile devices obtained general results functionality of the application is running as are expected.